Relación de las regalías mineras y el desarrollo del cantón Portovelo en Ecuador (Estudios) - Ulloa Sigcho, Wanner Manuel (2023)
This study intends to analyze the relation between mining and development in canton Portovelo as a process of social and economic change, highlighting the importance of mining revenues in the investments for the development of the canton. The investigation took place from a viewpoint considering sustainable development, economic development and mining, which allowed debate on how the territory is reconfigured due to extraction processes and arguments for and against extracting natural resources. Statistical and interview data provide the readers with a close picture of the situation of the income for the mining sector and the changes in the territories where mining takes place. The main findings prove that there are considerable changes at the social and environmental levels, but there is no return of resources from local mining activities. This means, this sector has not contributed to the construction of basic infrastructure for local development. However, large-scale construction has taken place, although using resources that are not redeemable as they focus on national development programs.